(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article addresses the development of an energy-efficient and environmentally friendly technology for heat supply systems. The purpose of the study is to design an autonomous heating system based on hydrogen energy and to evaluate its energy efficiency, technical parameters, and environmental advantages. The methodological framework includes a systematic engineering approach, thermodynamic analysis, and experimental modeling. During the study, the physical processes of hydrogen combustion, heat flow balance, and energy losses were determined. The obtained results show that the average efficiency (COP) of the system reached 85%, which is 10–15% higher compared to conventional electric and gas heating systems. Economic calculations demonstrated a reduction in operational costs by 20–25%. The system operates fully autonomously, with near-zero emissions of harmful substances. The developed technology can be effectively applied in residential buildings, schools, and laboratory facilities and represents an energy-efficient and environmentally sustainable solution suitable for the climatic conditions of the Kyrgyz Republic.